Modification of the Langendorff system of the isolated beating heart for experimental radiotherapy at a synchrotron: 4000 Gy in a heart beat. (18th May 2022) - Schültke, Elisabeth; Lerch, Michael; Kirschstein, Timo; Lange, Falko; Porath, Katrin; Fiedler, Stefan; Davis, Jeremy; Paino, Jason; Engels, Elette; Barnes, Micah; Klein, Mitzi; Hall, Christopher; et al.
Abstract : The modification of the Langendorff model of the isolated beating heart for microbeam irradiation studies and the results of the first pilot experiment, conducted at the Biomedical and Imaging beamline (IMBL) of the Australian Synchrotron, are reported. Abstract : Microbeam radiotherapy could help to cure malignant tumours which are currently still considered therapy‐resistant. With an irradiation target in the thoracic cavity, the heart would be one of the most important organs at risk. To assess the acute adverse effects of microbeam irradiation in the heart, a powerful ex vivo tool was created by combining the Langendorff model of the isolated beating mammalian heart with X‐Tream dosimetry. In a first pilot experiment conducted at the Biomedical and Imaging Beamline of the Australian Synchrotron, the system was tested at a microbeam peak dose approximately ten times higher than the anticipated future microbeam irradiation treatment doses. The entire heart was irradiated with a dose of 4000 Gy at a dose rate of >6000 Gy s −1, using an array of 50 µm‐wide microbeams spaced at a centre‐to‐centre distance of 400 µm. Although temporary arrhythmias were seen, they reverted spontaneously to a stable rhythm and no cardiac arrest occurred. This amazing preservation of cardiac function is promising for future therapeutic approaches.